(untitled) (Proceedings of the YSU C: Geological and Geographical Sciences, 2016)
The article provides a methodology for mapping of underground spaces. With regard to geographical and model diversity of underground spaces is proposed to include in the list of underground cavities that correspond to certain characteristics. This approach allows include in the list the most important spaces of underground objects, thereby improving the efficiency of cadastral works, especially records of such spaces, registration and restriction of property rights.